Effects of Pretreatment and Drying Conditions on Physical Properties and Bioactive Components of Garlic (Alium sativum) Powder (Tribhuvan University Journal of Food Science and Technology, 2024)
Garlic (Allium sativum) is rich in bioactive compounds but highly perishable. Drying is a key preservation method; however, inappropriate pretreatments and drying conditions often compromise its nutritional and functional quality. This study addresses the need to optimize these parameters to retain bioactive components while improving the physical properties of garlic powder for effective utilization as a functional food ingredient. The pretreatment of garlic cloves was carried out as follows: soaked in 0.2% potassium metabisulfite (KMS), citric acid (CA) solution, and distilled water (1:1w/v) for 10 min, followed by drying in a cabinet dryer at 45, 55, and 65°C, and ground using a coffee grinder and stored in aluminum coated plastic bags. Bioactive components, viz., antioxidant activity, total polyphenol, flavonoid, ascorbic acid, and physical properties, viz., bulk density, true density, porosity, and water absorption capacity, solubility index were analyzed. Antioxidant activity and total polyphenol content was highest for KMS-treated garlic dried at 55°C. Flavonoid content was highest for citric acid treated garlic cloves dried at 45°C and ascorbic acid was highest for KMS-treated and dried at 65°C. Physical properties of garlic powder found that drying at higher temperatures increased bulk density, true density, porosity, and water absorption capacity, but decreased solubility index. This study demonstrates that pretreatment and drying conditions significantly influence the physical properties and retention of bioactive components in garlic powder. Appropriate combinations of pretreatment and drying parameters can enhance physical properties while minimizing losses of bioactive components.